Exercise behavior education in children with heart disease: an application of the transtheoretical model. - Kuang I; Kao Y; Lee S (Journal of Evidence-Based Nursing, 2008)
The purpose of this study was to investigate the effect of exercise behavior education on the psycho-social factors of exercise behavior and on the stages of exercise among school children with heart disease. The study used a one group pretest-posttest design, and subjects were selected through judgment sampling. Subjects were all schoolchildren who had been diagnosed with heart disease. Most were in the fourth, fifth, and sixth grade at Beitou Elementary School in Taipei. Forty-one students completed the pretest-posttest. Structural questionnaires were distributed to students. Questions addressed demo-graphic variables, the cognitive scale of exercise, perceived benefits of exercise scale, perceived barriers to exercise scale, perceived self-efficiency of exercise scale, and stages of exercise. The educational interventions of exercise behavior used in the study applied the Transtheoretical Model's 'Processes of Change' in designing an exercise behavior educational plan for changing exercise behavior. The plan included activities for teaching and monthly visitations. Results show that exercise behavior educational interventions can significantly enhance exercise cognition and perceived exercise benefits. It further holds the potential to increase effectively the number of people engaged in regular exercise. However, results indicated no effect on decreasing perceived exercise barriers or promoting exercise self-efficacy. This study explored the effects of exercise behavior education intervention on children with heart disease. Results can be used as a reference in other related studies. Future studies may expand the area of focus to a wider range of schools and outpatient departments as well as design various exercise strategies in order to observe the differences in results achieved through different education intervention programs.